2009
DOI: 10.1128/jb.00540-09
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure, Determined by Nuclear Magnetic Resonance, of the b30-82 Domain of Subunit b of Escherichia coli F 1 F o ATP Synthase

Abstract: Subunit b, the peripheral stalk of bacterial F 1 F o ATP synthases, is composed of a membrane-spanning and a soluble part. The soluble part is divided into tether, dimerization, and ␦-binding domains. The first solution structure of b30-82, including the tether region and part of the dimerization domain, has been solved by nuclear magnetic resonance, revealing an ␣-helix between residues 39 and 72. In the solution structure, b30-82 has a length of 48.07 Å. The surface charge distribution of b30-82 shows one si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…Steady-state CD spectra were measured in far-UV light (185 to 260 nm) using a Chirascan spectropolarimeter (Applied Photophysics) as described previously (23). Circular dichroism (CD) spectroscopy of Mtε, Mtε-T19A, and Mtε-R37G (1.0 mg/ ml) and the peptide ε 103-120 (2.0 mg/ml) was performed in buffer A (50 mM Tris-HCl, pH 8.5, 200 mM NaCl, 10% glycerol) and buffer B (25 mM phosphate, pH 6.5, 50% TFE [4-chlorobutanol and 2,2,2-trifluoroethanol]), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Steady-state CD spectra were measured in far-UV light (185 to 260 nm) using a Chirascan spectropolarimeter (Applied Photophysics) as described previously (23). Circular dichroism (CD) spectroscopy of Mtε, Mtε-T19A, and Mtε-R37G (1.0 mg/ ml) and the peptide ε 103-120 (2.0 mg/ml) was performed in buffer A (50 mM Tris-HCl, pH 8.5, 200 mM NaCl, 10% glycerol) and buffer B (25 mM phosphate, pH 6.5, 50% TFE [4-chlorobutanol and 2,2,2-trifluoroethanol]), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Structures have been described of the F 1 domains of the enzymes from Escherichia coli (10, 11), Caldalkalibacillus thermarum (12), and Geobacillus stearothermophilus (formerly Bacillus PS3) (13); of the α 3 β 3 -subcomplex of the F 1 domain from G. stearothermophilus (14); and of isolated c-rings from the rotors of several species (15)(16)(17)(18)(19). There is also structural information on the peripheral stalk region of the F-ATPase from E. coli and on the N-terminal domain of the δ-subunit and its interaction with the N-terminal region of the α-subunit (20) and segments of the b-subunit (21)(22)(23).…”
mentioning
confidence: 99%
“…These basic residues are commonly found in the interface regions of monotopic membrane proteins, like . The E. coli subunit b dimer model ( a ) was built using the solution NMR structures of the membrane domain (residues 1-34) (1b9u.pdb) [Dmitriev et al 1999], the tether domain (residues 30-82) (2khk.pdb) [Priya et al 2009] and the X-ray structure of the dimerization coiled-coil domain (residues 62-122) (1ld2.pdb) [Del Rizzo et al 2002]. The δ-binding domain (δBD; residues 122-155) is not shown, but SAXS analysis [Priya et al 2008] revealed a boomerang-like shape in solution, similar to the mitochondrial F 1 F O -ATP synthase subunit b and the related H subunit of A 1 A O -ATP synthase.…”
Section: Positive Charges and The Interaction With Anionic Phospholipidsmentioning
confidence: 99%